Scalable, Nanometer‐Accurate Fabrication of All‐Dielectric Metasurfaces with Narrow Resonances Tunable from Near Infrared to Visible Wavelengths. Issue 9 (29th May 2022) - Prone, Giulia; Drechsler, Ute; Mayr, Christoph; Semenova, Olga; Thanner, Christine; Olziersky, Antonis; Eibelhuber, Martin; Mayor, Marcel; Lörtscher, Emanuel
Abstract : Dielectric metasurfaces are a class of flat‐optical elements that provide new ways to manipulate light. Irrespective of the underlying operation principle, the realization of such nanometer‐sized structures requires a high fabrication accuracy, e.g., to match resonant conditions. While electron‐beam lithography (EBL) achieves feature sizes below 10 nm, transparent substrates, as used for transmission devices, are challenging due to proximity effects. Furthermore, EBL's sequential exposure limits the exposable area, making it unaffordable for applications. Here, a novel fabrication route is described based on a master template created by EBL, which is then replicated by nanoimprint lithography (NIL). A three‐layer process enables high‐resolution nanoimprint resists with low etching selectivity with respect to semiconductors yet to be used. The resulting structures are highly reproducible and defect‐free thanks to the selective removal of residual layers and a master not suffering from proximity effects. Exemplarily, elliptical Mie resonators are fabricated with tunable resonances from the near infrared (NIR) to the visible wavelength regime. They reveal a high uniformity and sensitivity toward dielectric changes. The generic fabrication approach enables upscaling of nanoscale metasurfaces to wafer scales by step‐and‐repeat techniques and deployment of the optical devices fabricated in real‐world applications due to massively reduced costs. Abstract : Dielectric metasurfaces provide new ways to manipulate light offering promising novel applications. Mie resonators are fabricated with tunable resonances from near‐infrared to visible wavelength regime combining electron‐beam and nanoimprint lithography in a multilayer transfer process. Proximity effects could be reduced, and highly accurate devices fabricated in large areas. The process is generic and compatible with cost‐efficient large‐area patterning for real‐world applications.